Sediment Transport Model Quantifies Plume Length and Light Conditions From Mussel Dredging - Pastor, Ane; Larsen, Janus; Mohn, Christian; Saurel, Camille; Petersen, Jens Kjerulf; Maar, Marie (Frontiers in Marine Science, 2020)
Mussel dredging causes resuspension of sediment particles that reduce water clarity and potentially leads to reduced eelgrass growth. In order to study the impact of resuspension from mussel dredging on light conditions in the water column, field experiments were conducted at two sites in the Limfjorden. Light loggers were placed in two circular arrays around the dredge area. Vertical profiles of current velocity were measured by an ADCP and the sediment particle size composition was obtained from sediment core samples. The field data was used to force, calibrate and validate a sediment transport model developed in the FlexSem model system. Changes in sediment concentrations during and after mussel dredging were modelled for the two sites and for seven scenarios. We found that the distance and direction of the plume in the model was in good agreement with light logger data. The plume duration was less than 1 hour, and the impact range was between 260-540 m. The scenarios showed that fishing intensity and current speeds were most important for shaping the sediment plumes. Changes in suspended sediment concentrations were 0.62 to 1.79 mg/l on median average and 1.22 to 11.61 mg/l for the upper quantile of the plume, which were on the same order of magnitude as background values in the Limfjorden. The amount of fishing days during the eelgrass growth season was 6-8% in Lovns Bredning and 16-35% in Løgstør Bredning and less than 1-2% of the total area was dredged per season. Even though there are substantial changes in the light conditions from the sediment plumes, the overall spatio-temporal impact in the study area is considered low. We recommend that management plans in other areas could sustain a shellfish fishery by limiting fishing intensity and frequency near eelgrass beds. The presented approach combines observational data, sediment transport modelling and reported fishing activity. It is a step forward within sediment transport modelling and could be incorporated into environmental impact assessments. The results have recently been used as scientific background for recommendations to improve the management plans according to the Danish Mussel Policy and relevant EU Directives.